PENGATURAN TENTANG REKLAMASI PANTAI BERDASARKAN UNCLOS 1982 DAN IMPLEMENTASINYA DI INDONESIA - Azizah, Siti (Jurnal Yuridis, 2016)
Reclamation can be interpreted as an effort to land acquisition by drying the swamp, tidal areas, and so on. International In not a few countries that do the reclamation to conflict with state borders. In Indonesia too many cases of reclamation hurt some parties. Method used in this paper is a normative research methods. Data collection method in this paper the author uses the method of literature. International law has not set the reclamation significantly, but in the national law in Indonesia has been regulated in Law Number 27 of 2007 on the management of coastal areas and small islands. The importance of the rules regarding the reclamation it is expected that international law can be set significantly.